Incorporation of chromium residue from tannery in black and red clay - Wagner , Caroline; Costa , Raphaela Moreira; Souza , Tânia Regina de; Lugokenski, Thiago Henrique (Seven Editora, 2023)
Brazil has a large amount of clay reserves scattered throughout the country, but due to environmental awareness, restrictive laws and conservation units there is a restriction of the availability of this mineral resource. In addition, ceramics are widely studied for waste encapsulation, aiming at cost benefit and sustainability. One of these residues is chromium from leather tanning, it has polluting characteristics mainly because it contains Chromium (Cr)III. This work aimed to study the feasibility of incorporating tannery residue in ceramic materials, using different clays. For this, two types of clay were selected and incorporated 0, 1 and 2% of tannery residue with 8.03% of Cr, molded ceramic bodies, and then extruded. The bodies were dried and burned at temperatures of 900ºC and 1050ºC. The characterization of the raw materials showed through the limits of Atterberg that red clay is more plastic than black clay. In general, the results of incorporation of residues in red clay were better than in black clay. In fact, the red clay in the presence of tannery residue showed lower linear retraction, lower water absorption, less mass loss to fire and rupture tension. Thus, as for the addition of chromium, associated with temperatures of 1050º C it can be said that the ceramics made of red clay had their characteristics improved, without changing the plasticity parameters and the physicochemical properties of the tested ceramics. This study shows a feasibility for an ecologically more appropriate destination of tannery waste. DOI:https://doi.org/10.56238/uniknowindevolp-057